Mortality Rates in the General Irish Population Compared to those with an Intellectual Disability from 2003 to 2012. - MCCARRON, MARY; CARROLL, RACHEL (My University, 2015)
BACKGROUND: Historically, there has been higher and earlier mortality among people with intellectual disability as compared to the general population, but there have also been methodological problems and differences in the available studies. METHOD: Data were drawn from the 2012 National Intellectual Disability Database and the Census in Ireland. A standardized mortality ratio (SMR) was calculated, as well as average age at death. Ratios and differences were further examined for the influence of age, gender and level of intellectual disability. RESULTS: Mortality in persons with intellectual disability was four times higher and they were, on average, dying 19 years earlier than peers in the general population. Women with intellectual disability were living longer than males with intellectual disability, but differences in survival as compared to the general population were greater for these women. There was little change in average age at death over 10 years, and death was earlier the more severe the level of intellectual disability. DISCUSSION: The use of mortality ratios rather than average age at death alone is recommended, as well as greater standardization in use of data sets including the whole population, given high levels of earlier deaths in people with intellectual disability.
PUBLISHED
Keywords: Ireland; National Intellectual Disability Database; intellectual disabilities; mortality data